On the mechanisms of consumption of calcium lignosulfonate by cement paste. (August 2017) - Colombo, A.; Geiker, M.; Justnes, H.; Lauten, R.A.; De Weerdt, K.
Abstract: The aim of this paper is to assess the mechanisms of consumption of softwood calcium lignosulfonate (LSs) by cement paste. The LSs consumption by two different cements (CX and ANL) and two reference materials (CaCO3 and Ca(OH)2 ) was investigated, either by adding the LSs immediately with the mixing water (IA) or after 10 min of hydration (DA). For IA, the increase in LSs dosage caused additional ettringite formation and an increase in particle surface area. This was not observed for DA. Since no AFm phase could be detected, intercalation in AFm seemed not to occur for the investigated materials. The main mechanism of LSs consumption for CX cement (both for IA and DA) and for ANL cement (only for DA) appeared to be monolayer adsorption. For IA, the amount of consumed LSs could not be ascribed exclusively to monolayer surface adsorption and other LSs consumption mechanisms might play a role.